Analysis of the Influence of the Regulation on the Ability of Communication Health Officer at Dr Wahidin Sudirohusodo General Hospital - Nur Sri Widyastuti; Yusriani Yusriani; Andi Nurlinda (Sean Institute, 2023)
Health promotion is a core quality issue to raise awareness and maintain quality of life. Standards for health promotion in hospitals are needed to ensure the quality of services provided. Therefore, WHO formed a working group at the 9th International Conference on Health Promotion Hospitals, Copenhagen, in May 2001. This study aims to analyze the effect of the regulations on the communication skills of health officers at Dr. Wahidin Sudirohusodo General Hospital, Makassar. This study uses a quantitative research design using a cross-sectional approach. The population and sample in this study are health officers and inpatients at Dr. Wahidin Sudirohusodo General Hospital, Makassar. Based on the results of bivariate analysis using the Chi-square test, it is concluded that there is a significant effect of regulation on the communication skill abilities of health officers. It is hoped that the hospital will improve the quality of hospital health promotion implementation through health promotion training such as effective communication training and hospital health promotion management.